Modulating Nitric Oxide Dioxygenase and Nitrite Reductase of Cytoglobin through Point Mutations - John Ukeri; Michael T. Wilson; Brandon J. Reeder (MDPI AG, 2022)
Cytoglobin is a hexacoordinate hemoglobin with physiological roles that are not clearly understood. Previously proposed physiological functions include nitric oxide regulation, oxygen sensing, or/and protection against oxidative stress under hypoxic/ischemic conditions. Like many globins, cytoglobin rapidly consumes nitric oxide under normoxic conditions. Under hypoxia, cytoglobin generates nitric oxide, which is strongly modulated by the oxidation state of the cysteines. This gives a plausible role for this biochemistry in controlling nitric oxide homeostasis. Mutations to control specific properties of hemoglobin and myoglobin, including nitric oxide binding/scavenging and the nitrite reductase activity of various globins, have been reported. We have mapped these key mutations onto cytoglobin, which represents the E7 distal ligand, B2/E9 disulfide, and B10 heme pocket residues, and examined the nitric oxide binding, nitric oxide dioxygenase activity, and nitrite reductase activity. The Leu46Trp mutation decreases the nitric oxide dioxygenase activity > 10,000-fold over wild type, an effect 1000 times greater than similar mutations with other globins. By understanding how particular mutations can affect specific reactivities, these mutations may be used to target specific cytoglobin activities in cell or animal models to help understand the precise role(s) of cytoglobin under physiological and pathophysiological conditions.